2024
DOI: 10.1002/alz.13610
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk score for Alzheimer's disease predicts brain volume differences in mid and late life in UK biobank participants

Peter T. Buto,
Jingxuan Wang,
Renaud La Joie
et al.

Abstract: INTRODUCTIONWe estimated the ages when associations between Alzheimer's disease (AD) genes and brain volumes begin among middle‐aged and older adults.METHODSAmong 45,616 dementia‐free participants aged 45–80, linear regressions tested whether genetic risk score for AD (AD‐GRS) had age‐dependent associations with 38 regional brain magnetic resonance imaging volumes. Models were adjusted for sex, assessment center, genetic ancestry, and intracranial volume.RESULTSAD‐GRS modified the estimated effect of age (per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Our results are in concordance with prior investigations which suggested potential correlations between the AD-PRS and the pathological progression within the hippocampal region [12,15] and structural alterations in the brain [16-18]; moreover, our results are consistent with ndings from post-mortem examinations indicating age-related impacts of AD-PRS on the entorhinal cortex and frontal lobes [13]. Additionally, our study revealed that AD-PRS-associated degenerative alterations occur earlier in deeper brain regions, a phenomenon that has been corroborated by a recent study based on the UKB cohort [17], con rming the hypothesized spreading pattern of pathological proteins of AD [2,50].…”
Section: Age-related Structural Differences Offer Insights Into Precl...supporting
confidence: 92%
See 4 more Smart Citations
“…Our results are in concordance with prior investigations which suggested potential correlations between the AD-PRS and the pathological progression within the hippocampal region [12,15] and structural alterations in the brain [16-18]; moreover, our results are consistent with ndings from post-mortem examinations indicating age-related impacts of AD-PRS on the entorhinal cortex and frontal lobes [13]. Additionally, our study revealed that AD-PRS-associated degenerative alterations occur earlier in deeper brain regions, a phenomenon that has been corroborated by a recent study based on the UKB cohort [17], con rming the hypothesized spreading pattern of pathological proteins of AD [2,50].…”
Section: Age-related Structural Differences Offer Insights Into Precl...supporting
confidence: 92%
“…Although APOE gene polymorphism has been acknowledged as the most powerful genetic factor contributing to sporadic AD, the dependence of APOE effects from the in uence of AD-PRS on changes in brain structures in preclinical stages remains unclear. Studies supporting the dependence have demonstrated associations between APOE and levels of pathological markers in CSF [54], as well as links to WM integrity and WMHV [21], and suggested that the exclusion of APOE loci or regions from AD-PRS would decrease its statistical power in explaining variations in brain volumes [17,55] and WM integrity [16]. Conversely, other studies suggested that the effects of the AD-PRS on Aβ burden [14,19], tau burden [13,14,56], brain structure changes [13,16,21] and cognitive function [18, 56] might be independent of APOE.…”
Section: Apoe and The Ad-prsmentioning
confidence: 99%
See 3 more Smart Citations